A corpus-based comparative study of exemplification in hard and soft sciences research articles: a case of Chinese and English authors - Yuanyuan, Yang; Noor Mala Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Exemplification, an essential part of argumentation in academic writing, helps authors to support general ideas with specific examples. This corpus-based investigation is a preliminary comparative study on the use of exemplification by Chinese and English native authors in research articles (RAs) of hard sciences and soft sciences covering six different disciplines. The study focuses primarily on three aspects: Exemplifying Markers (EMs), exemplifying units, and functions of exemplification. A corpus of twelve RAs with a total number of 143,604 words across six disciplines was built with six articles each from the hard sciences and the soft sciences. Triki’s (2021) model of exemplification was used as the analytical framework. The exemplification theory serves as the theoretical basis for the study and K-means clustering and Welch Two Sample t-tests are employed as the research methods. Findings show that diverse categories of EMs are used by authors from these two different linguistic backgrounds and in different disciplines. It is also revealed that the authors from the two linguistic backgrounds use EMs more similarly in hard sciences than in soft sciences, even though EMs are usually used more frequently in the soft sciences. In addition, there are significant differences in the use of EMs between the two groups of authors and different disciplines. More exemplifying groups than exemplifying clauses are employed across linguistic backgrounds and disciplines. Various categories of functions are performed by exemplification. The findings may be valuable in guiding exemplification instruction and learning in English for Academic Purposes (EAP) environments.